Different faces of participation: Social involvement in rural planning in Poland - Bednarek-Szczepańska, Maria; Mazurek, Damian (Quaestiones Geographicae, 2025)
The article deals with public participation in two dimensions of local rural planning: development and spatial planning. The research consisted in determining, with the help of constructed indexes, the level of participation of rural residents in various planning processes and the factors that explain the variation in the level of participation. Spatial, demographic and social factors were examined, as well as the importance of location in different functional types of areas and historically diverse regions. The study analysed 148 municipalities selected from four regions of Poland for which data on the residents’ participation in 367 planning processes were obtained. Two types of documents were selected for the identification of factors differentiating the level of participation: local development strategies and land use plans. The level of residents’ involvement in strategic planning was not statistically related to demographic, spatial or even social capital variables. On the other hand, with regard to residents’ involvement in spatial planning, the relationships with demographics and the functional type of municipality are clearly visible, with the highest correlations of the level of participation with the level of education of the municipality’s residents and migration inflow.